Dopamine Transporter 3′-UTR VNTR Genotype and ADHD: a Pharmaco-Behavioural Genetic Study with Methylphenidate - Joober, Ridha; Grizenko, Natalie; Sengupta, Sarojini; Amor, Leila Ben; Schmitz, Norbert; Schwartz, George; Karama, Sherif; Lageix, Philippe; Fathalli, Ferid; Torkaman-Zehi, Adam; Stepanian, Marina Ter (Neuropsychopharmacology (New York, N.Y.), 2007)
We sought to test the hypothesis that the variable number of tandem repeat (VNTR) polymorphism in the 3′-untranslated region (3′-UTR) of the SLC6A3 gene modulates behavior in children with ADHD and/or behavioral response to methylphenidate (MPH). One hundred and fifty-nine children with AHDH (6–12 years) were assessed with regard to the Conners’ Global Index for parents (CGI-Parents) and teachers (CGI-Teachers) and the response of these behaviors to MPH (0.5 mg/kg/day) using a 2-week prospective within-subject (crossover) trial. Based on CGI-Parents, the profile of behavioral response to MPH as compared to placebo was not parallel in the three groups of children separated according to their genotype in the 3′-UTR VNTR polymorphism of SLC6A3, as indicated by a significant ( p =0.017) genotype by treatment two-way interaction. Individuals having the 9/10 and 10/10 genotypes displayed a significant positive response to MPH as opposed to those homozygous for the 9-repeat allele. No genotype or genotype by treatment interaction was observed for CGI-Teachers. These findings support a role for the DAT gene 3′-UTR VNTR polymorphism in modulating the response of some behavioral dimensions to MPH in children with ADHD. They also suggest the presence of genetic heterogeneity that could be indexed by the quality of behavioral response to MPH.